A Herman Ottó Kárpát-medencei Biológia Versenyfelkészítő hétvége kárpátaljai tapasztalatai - Kohut Erzsébet; Когут Ержебет; Kohut Erzsebet; Hadnagy István; Гаднадь Іштван; Hadnagy Istvan; Takács Gabriella; Токач Габріелла; Kolozsvári István; Коложварі Степан (Видавництво «Код», 2023)
A Herman Ottó Biológia Verseny Magyarországon nagy múltra tekint vissza, 2023-ban már 33. alkalommal hirdette meg a Magyar Természettudományi Társulat. A versenykiírásnak megfelelően magyarországi és külhoni 13‒14 éves, 7‒8. osztályos tanulók vehetnek részt a megmérettetésben.

Резюме. Талант – наш найбільший природний скарб. Виявлення таланту та його розвиток є одним із найважливіших завдань педагога. Забезпечення розвитку таланту в усіх його формах для національних меншин є життєво важливим питанням. У нашій статті ми представляємо комплексну практику підготовки талановитих учнів, організовану Закарпатським угорськомовним педагогічним товариством та Благодійним фондом «ГЕНІУС», яка відбувається в позашкільний час і призначена для підготовки учнів до біологічного конкурсу ім. Германа Отто. Програма триває дев'ять днів (тричі по три вихідних) за підтримки угорської держави. Протягом цих вихідних запрошені учні ознайомлюються з навчальною програмою, визначеною для конкурсу та доповнену знаннями специфічними для нашого регіону, Карпатського басейну. Отримані знання, навички ми систематично оцінюємо. Під час визначених вихідних, дотримуючись принципів, визначених Пассовим (Passow), ми зосереджуємося насамперед на збагаченні кількісних і якісних знань, крім того, ми прагнемо розвивати ефективні стратегії навчання.

Abstract. Talent is our greatest natural treasure. Identification of talent and its development is one of the most important tasks of a teacher. Ensuring the development of talent in all its forms for national minorities is a vital issue. In our article, we present the comprehensive practice of training talented students, organized by the Transcarpathian Hungarian-speaking Pedagogical Society and the «GENIUS» Charitable Foundation, which takes place outside of school hours and is designed to prepare students for the biology competition named after Hermann Otto. The program lasts nine days (three times with three weekends) with the support of the Hungarian state. During this weekend, the invited students familiarize themselves with the curriculum defined for the competition and supplemented with knowledge specific to our region, the Carpathian Basin. We systematically evaluate the acquired knowledge and skills. During the designated weekend, following the principles defined by Passow, we focus primarily on the enrichment of quantitative and qualitative knowledge, in addition, we strive to develop effective learning strategies. Our goal is to present and demonstrate the preparation program for the Hermann Otto Biology Competition, which took place in 2017-2023, as well as the practice of its implementation and the basis of the experience gained. In the first part, we describe the method of student selection, and in the second – the thematic program. In the final part, we summarize the experience gained and consider the possibilities of further development. The program provides participants with an excellent opportunity to get acquainted not only with the traditional methods of knowledge transfer and assessment, common in our country, but also with the methods used in a neighboring country of the European Union. In addition to expanding their knowledge, students can gain experiences that will increase their self-confidence and they can see their future further education opportunities in a broader perspective. An international test of their knowledge can become a motivation for students and influence their school achievements in their home country. By sharing their impressions and experiences, they can also become a motivating force for their classmates. Modern prospects for the development of the educational system of Ukraine are aimed at the implementation of systems that already exist in the countries of the European Union. The named competition is aimed at the Central European level, and it corresponds to Ukrainian principles, since in the finals students can meet, compete and get to know each other from different countries (such as Hungary, Slovakia, Romania, etc.).
Досвід роботи підготовчого позанавчального процесу з Біологічного конкурсу імені Германа Отто Карпатського Басейну
The Experiences of the Herman Ottó Carpathian Basin Biology Competition Preparation Weekend in Transcarpathia
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00011820
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-5
Keywords: Herman Ottó Kárpát-medencei Biológia Versenyfelkészítő; Genius Jótékonysági Alapítvány; Kárpátaljai Magyar Pedagógusszövetség; tehetséggondozás; Kárpátalja